Characterization, source and risk assessments of sediment contaminants (PCDD/Fs, DL-PCBs, PAHs, PCBs, OCPs, metals) in the urban water supply area. (August 2022) - Güzel, Barış; Canlı, Oltan; Çelebi, Ahmet
Abstract: Water resources are becoming more valuable day by day. They need to evaluate the pollution and risk situations of the sources that supply water in detail. It is aimed to determine the level of POPs (PCDD/Fs, DL-PCBs, PAHs, PCBs, and OCPs) and metals, which are persistent pollutants, in the surface sediments taken from Yuvacık lake to reveal their possible sources, and to make toxicological and ecological risk assessments of sediment quality. It is one of the most comprehensive studies on the sediment scale for a drinking water source and is a first for the study area. Seventeen 2, 3, 7, 8-substituted PCDD/Fs were analyzed with US EPA method (M.1613). The concentrations of all POPs were determined by GC-MS/MS. The range of ∑PCDD/F is 3.171 (Y8) to 28.42 (Y10) pg/g, with the highest concentrations of OCDD and 1234678-HpCDF compounds. Total DL-PCB concentrations 6.369 (Y8) to 37.41 (Y9) pg/g Total PAH concentrations in the samples ranged from 36.97 ng/g (Y1) to 81.38 ng/g (Y10). The PAH compounds with the highest concentrations at all sampled points were Phenanthrene 3141 (Y7) - 21, 636 (Y10) and Naphthalene (11.40–19.41) ng/g. Total OCP concentrations ranged from 1.045 ng/g (Y8) to 4.179 ng/g (Y2), while total PCB concentrations ranged from 0.308 (Y1) to 1.55029 (Y9) ng/g. DDT p, p (0.4078–3.2544 ng/g) has the highest concentration among OCPs. PCB 101, 153, 138, and 180 are the highest detected PCB congeners. As a result of the source analysis, three different main sources were determined for all pollutant groups. They show accumulation in the sediment as a result of long-distance atmospheric transport. Toxicological values were found below acceptable limits. The main metals posing ecological risk were Ag, Cu, and Cd. Monitoring of POPs and assessing their toxicological and ecological risks are important for planning water resources and should be applied especially for critical basins. Graphical abstract: Image 1 Highlights: PCDD/Fs and other POPs are transported long distances. POPs are accumulating in water-supplied areas and should be considered. Sediments in water sources are accumulation areas for persistent pollutants. Sediment is an essential component in ecological risk assessments for water resources.